Proximity as urban democratic legitimacy: Strategies of participation in Buenos Aires - Halvorsen, Sam (2024)
Since 2007, Buenos Aires has been governed by a centre-right coalition that has made participationan integral part of its approach to governance. Under mayor Horacio Rodrı´guez Larreta(2015–2023), the idea and practice of proximity became central, notably through weekly meetingswith neighbours across the city. This article demonstrates that proximity was a strategy for buildingurban democratic legitimacy. In so doing, it introduces the work of Pierre Rosanvallon to anurban studies readership. Contemporary literature on urban participation is at risk of establishingontologically fixed positions, as seen in recent debates on the ‘post-political city’. Rosanvallon’slegitimacy of proximity is an analytical device that provides an open and non-essential reading ofparticipation. Based on extensive qualitative research, the article examines how and why Larretaand his city government deployed the strategy of proximity, while also highlighting its limits.